J. Wagner correspondence - Wagner, J., active 1794.
ALS written by Wagner, an assistant to the U.S. secretary of state, Edmund Randolph, to William Taylor, merchant of Baltimore, Md., concerning the British capture of the brig Eliza whose cargo Taylor owned.
Public official.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Randolph, Edmund, -- 1753-1813.; Taylor, William -- (Merchant) -- Correspondence; Eliza (Brig : 1793-1795); United States. -- Department of State -- Officials and employees; Privateering -- Great Britain; Public officials